Pentingnya Pendidikan Akhlak dalam Kehidupan Masyarakat Islam - Mgr Sinomba Rambe; Waharjani Waharjani; Djamaluddin Perawironegoro (Tadarus Tarbawy Jurnal Kajian Islam dan Pendidikan, 2023)
The importance of maintaining Ukhuwah Islamiah among people who are currently experiencing moral degradation. The phenomenon of lack of mutual respect, indifference between members of society, lack of tolerance, and fading of mutual cooperation are the main problems of Islamic society today. The research entitled "The Importance of Moral Education in Community Life" is a qualitative research with a literature study approach. Where researchers will refer to several books, scientific works (journals), and books that discuss strengthening morals in society. The results of this study reveal that it is important to learn and practice moral education in a society that is oriented towards the verses of the Koran and the Prophet's Hadith as a reflection of its implementation, such as answering greetings, answering people who sneeze, fulfill invitations, visit thsick, give each other advice, and participate. Take the jenazah to the cemetery. This aims to create an Islamic society and synergy